Cerebral Aspergillosis in an Immunocompetent Patient after COVID-19 Infection - Almeida, Laryssa C. Azevedo; Braga, Henrique Moura; Costa, Bruno Silva (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Fungal brain abscesses are an uncommon condition in the immunocompetent population, especially due to the etiologic agent Aspergillus sp. The emerging coronavirus disease 2019 (COVID-19) pandemic brought about neurological manifestations that were previously little known, caused by the direct manifestations of the virus, as well as by the therapy itself, with hospitalization and use of corticosteroids. This manuscript highlights the need for attention in the management of patients with neurological disorders and history of COVID-19 infection. In the current paper, we report the case of a patient without comorbidities who presented multiple brain abscesses caused by Aspergillus fumigatus, after infection by Severe Acute Respiratory Syndrome Coronavírus 2 (SARS-CoV-2).
Keywords: neuroaspergillosis; brain abscess; COVID-19; aspergillosis